Unit test code generator for lua programming language - Wibowo, Junno Tantra Pratama; Hendradjaya, Bayu; Widyani, Yani (ICODSE 2015 : proceedings of 2015 International Conference on Data and Software Engineering : Universitas Gadjah Mada, Indonesia, November 25th-26th, 2015, 2015)
Software testing is an important step in the software development lifecycle. One of the main process that take lots of time is developing the test code. We propose an automatic unit test code generation to speed up the process and helps avoiding repetition. We develop the unit test code generator using Lua programming language. Lua is a fast, lightweight, embeddable scripting language. It has been used in many industrial applications with focuses on embedded systems and games. Unlike other popular scripting language like JavaScript, Python, and Ruby, Lua does not have any unit test generator developed to help its software testing process. The final product, Lua unit test generator (LUTG), integrated to one of the most popular Lua IDE, ZeroBrane Studio, as a plugin to seamlessly connect the coding and testing process. The code generator can generate unit test code, save test cases data on Lua and XML file format, and generate the test data automatically using search-based technique, genetic algorithm, to achieve full branch coverage test criteria. Using this generator to test several Lua source code files shows that the developed unit test generator can help the unit testing process. It was expected that the unit test generator can improve productivity, quality, consistency, and abstraction of unit testing process.